2003
DOI: 10.2337/diacare.26.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Pregnancy Among Immigrant Women With Diabetes

Abstract: OBJECTIVE—We studied outcome of pregnancy among immigrant women with diabetes. The women came from regions of the world with high incidence of impaired glucose tolerance and type 2 diabetes. Prevalences, secular trends, and sociodemographic risk factors of diabetes were also explored. RESEARCH DESIGN AND METHODS—Data from the Medical Birth Registry of Norway on all births from 1988 to 1998 for mothers born in South Asia and North Africa (11,268) and Norway (601,785) were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 24 publications
(22 reference statements)
5
31
0
2
Order By: Relevance
“…The relatively small sample precluded a detailed statistical analysis comparing Caucasian and nonCaucasian groups. The study by Vanger et al carried out in Denmark reported higher incidences of adverse outcome in the non-Caucasian women, but these differences were not statistically significant in the small groups [24].…”
Section: Discussionmentioning
confidence: 96%
“…The relatively small sample precluded a detailed statistical analysis comparing Caucasian and nonCaucasian groups. The study by Vanger et al carried out in Denmark reported higher incidences of adverse outcome in the non-Caucasian women, but these differences were not statistically significant in the small groups [24].…”
Section: Discussionmentioning
confidence: 96%
“…Diabetes depending on the type and severity increases the risk of adverse birth outcomes such as macrosomatia, low birth weight, prematurity, fetal death, and congenital anomalies. 22,35 In general, more severe stages of diabetes are associated with vascular compromise and smaller than expected birth weights. In a study of pregnancy outcomes among South Asian women in Norway, the prevalence of pregestational diabetes was almost twice as high as in Norwegians.…”
Section: Discussionmentioning
confidence: 99%
“…Elles sont plus âgées et plus en surpoids. Elles sont également plus souvent issues de l'immigration comme cela a été rapporté par Vangen [10] et de conditions socioéconomiques défavorables. Elles cumulent donc, outre le diabète lui-même, des facteurs de risque périnatal.…”
Section: Discussionunclassified